Emotional Tissue: A Visual Representation of Characters' Emotional States in Games - Luz Junior, Jonas; Rodrigues, Maria (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
In empathy games, the representation of the character's emotional states during the narrative is relevant. For this purpose, the designer of empathy games uses different resources, such as the game's graphical style, sound and visual effects, soundtrack mood, and narrative style and pace, among others. Although these can effectively transmit emotion, they will still be subject to the player's interpretive subjectivity. However, there are situations where the designer wants the player to understand the character's emotional state, especially when it is the focus of gameplay and fundamental to the player's decisions. Unlike conventional level bars and their visual variations to represent characters' emotional states, this work presents a new approach for defining a widget to express emotional states, modelled as an organic structure in the form of a shaded cloth deformation. We directly relate its pulse frequency to the intensity of the characters' emotions and its colours to the characters' feelings defined by the game designer. In addition, we conducted a preliminary performance comparative study with the widget configured with four, six and eight emotions and created demonstration scenes to validate its use.